A lightweight IoT‐based security framework for inventory automation using wireless sensor network. (29th October 2019) - Batra, Isha; Verma, Sahil; Kavita,; Alazab, Mamoun
Summary: Internet of things (IoT) has evolved as an innovation of next generation in this world of smart devices. IoT tends to provide services for data collection, data management, and data and device security required for application development. Things or devices in IoT communicate and compute to make our lives comfortable and safe. In inventory automation, real‐time check on items, their information management, and status management, monitoring can be carried out using IoT. The huge amount of data that flows among the devices in the network demands for a security framework that ensures authentication, authorization, integrity, and confidentiality of data. The existing security solutions like SIMON or SPECK offer lightweight security solutions but are vulnerable to differential attack because of their simplicity. Moreover, existing solutions do not offer inbuilt authentication. Therefore, this research work contributes a secure and lightweight IoT‐based framework using wireless sensor network (WSN) as a technology. The existing security solutions SPECK and SIMON are compared with the proposed security approach using COOJA simulator. The results show that proposed approach outstands others by 2% reduction in number of CPU cycles, 10% less execution time, 4% less memory requirements of security approach, and with minimum 10% more security impact. Abstract : Internet of things (IoT) demands for a security framework that ensures authentication, authorization, integrity, and confidentiality of data. This research work contributes a secure and lightweight IoT framework using wireless sensor network as a technology. The existing solutions SPECK and SIMON are compared with the proposed approach using COOJA simulator. The results show that proposed approach outstands by average 2% reduction in number of CPU cycles, 10% less execution time, 4% less memory requirements, and with minimum 10% more security impact.